Paronychia revoluta, a new species of caryophyllaceae from Brazil - Carneiro, Cláudia Elena; Furlan, Antonio [UNESP] (My University, 2004)
A new species of Paronychia, P. revoluta, from the state of Rio Grande do Sul, Brazil, is described and illustrated. This species is closely related to P. camphorosmoides, distinguished from it by linear-subulate leaves with a revolute margin and prominent midribs. It is also allied to P. fasciculata, from which it differs in the lanceolate, acuminate, fimbriate, and whitish stipules, and linear-subulate leaves.
Keywords: Brazil; Caryophyllaceae; Paronychia